Construire la mémoire et l’identité autochtones aux États-Unis. Le documentaire photographique Project 562 de Matika Wilbur - Aurélie Journée (IdeAs)
Through the analysis of the photographic series Project 562 created by Indigenous North American artist Matika Wilbur, our study aims to question the concept of « photographic documentary » regarding Indigenous representations of themselves. Our presumption is that the formal aspects of these photographic narratives raise, in their specific historical and cultural contexts of production, issues about Indigenous memory and identity in the United States. Our analysis is linked to our PhD research that questions the potential of photography as a tool for political and social claims. More specifically, our research tries to highlight that Indigenous women artists in North America use the photographic medium in order to criticize Western epistemology, sciences and techniques from a decolonial perspective. This paper aims to trace, through an historical, anthropological and cultural approach of the photographic image, the context of production of Matika Wilbur’s Project 562 and its goals. Then, we will see how its creative process and its own formal modalities update a historically Western practice while valuing Indigenous cultures. In conclusion, we will question what this project reveals about the place and role of Indigenous women in contemporary society.